Meningkatkan komitmen bagi Aparatur Sipil Negara: Perspektif teori pertukaran sosial dalam akuntabilitas organisasi publik - Adi Putranto, Ricky; Andikaputra, Fikri Aditya Tri; Pradesa, Hafid Aditya; Priatna, Ramdani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Organizational commitment is an important form of attitude from an employee towards his organization. The purpose of this study is to examine the importance of organizational commitment from the perspective of social exchange theory. With a social exchange perspective, the research model was built by integrating perceptions of organizational support and job satisfaction into having an impact on organizational commitment. The context of the situation during the pandemic has its own color in this study, especially with situations that require various jobs to be carried out remotely or away from home, so the extent to which employees remain committed to their organizations from the perspective of social exchange. This study takes a sample of ASN who are working in the Bandung Raya area. The data analysis technique uses path analysis, which aims to examine the effect of perceived organizational support on organizational commitment directly or indirectly through job satisfaction. The results showed that every relationship between variables found that the beta coefficient value was in the significant category. This confirms that empirically, social exchange theory can apply in pandemic conditions, especially in building ASN commitment to their organizations as a manifestation of the accountability of public sector organizations.